Ceramic nano composite yarn guide material as well as preparation method and application thereof

Through the ceramic nanocomposite wire guide material and optimization process, the problem of insufficient wear resistance and interface bonding strength in textile wire guide is solved, which significantly improves the service life and production efficiency of the equipment, and meets the high-speed operation environment. need.

CN119192724AInactive Publication Date: 2024-12-27苏州芯合半导体材料有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411334641.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional polymer-based composite materials have poor wear resistance and weak interface bonding strength in textile wire guides, resulting in short service life and low production efficiency, especially when running at high speed, wire breakage and winding failures are prone to occur.

Method used

Using ceramic nanocomposite wire guide materials, including polypropylene resin, silane coupling agent surface modified alumina nanoparticles, carbon fiber reinforced phase and silica, a dense wear-resistant layer is formed through ion bombardment, and the group distribution ratio and process parameters are optimized. , improve the wear resistance of the material and the interface combination strength.

Benefits of technology

It significantly improves the service life and working reliability of textile wire guides, enhances the wear resistance and friction coefficient of the material, meets the requirements of high-speed working environment, extends the service life of the equipment and reduces the failure rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057936590000171
    Figure BDA0005057936590000171
  • Figure BDA0005057936590000172
    Figure BDA0005057936590000172
Patent Text Reader

Abstract

The invention provides a high-strength ceramic-based composite material as well as a preparation method and application thereof. The high-strength ceramic-based composite material comprises the following components in parts by weight: 60-70 parts of polypropylene resin; 20 to 25 parts of silane coupling agent surface modified aluminum oxide nano particles; 8-12 parts of a carbon fiber reinforced phase; 1-3 parts of silicon dioxide; 0.5 part of other auxiliary agents; a compact wear-resistant layer is formed on the surface of the ceramic nano composite yarn guide material through ion bombardment treatment, so that the wear resistance, the interface bonding strength and the friction coefficient of a PP (polypropylene)-based composite material are improved, and a material solution with better performance is provided for the application field of spinning yarn guides with high wear requirements; and the service life and the working reliability of the spinning yarn guide are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile yarn guides, and in particular to a ceramic nano-composite yarn guide material and a preparation method and application thereof. Background Art

[0002] In the field of materials science, the research and development and application of composite materials have always been an important driving force for the advancement of industrial technology. With the rapid development of industries such as textiles, machinery, and electronics, the requirements for material performance are increasing, especially in terms of wear resistance, interface bonding strength, and stability under specific working environments. Traditional polymer-based composite materials, such as polypropylene (PP)-based composite materials, have the advantages of low cost and good processing performance, but their performance is often difficult to meet the requirements when facing extreme working conditions such as high wear and high-speed operation.

[0003] Specifically, when polypropylene (PP)-based composite materials are used as key components such as textile yarn guides, they often have poor wear resistance and large volume loss due to problems such as insufficient surface hardness and weak interface bonding with fillers, which seriously affects the service life and production efficiency of the equipment. In addition, during high-speed operation, traditional yarn guide materials have insufficient friction coefficients, making it difficult to ensure stable transmission of yarns, increasing the risk of failures such as breakage and entanglement.

[0004] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application, nor does it necessarily provide technical guidance. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0005] In order to solve the technical problems such as the deficiencies in wear resistance, interface bonding strength and adaptability to specific working environments of current composite materials, the present invention proposes a ceramic nano-composite wire guide material and its preparation method and application, which improves the wear resistance, interface bonding strength and friction coefficient of PP (polypropylene) based composite materials, provides a material solution with better performance for the application fields with high wear requirements of textile wire guides, and greatly improves the service life and working reliability of textile wire guides.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] In one aspect, the present invention provides a ceramic nanocomposite wire guide material, comprising the following components in parts by weight: 60-70 parts of polypropylene resin; 20-25 parts of alumina nanoparticles surface-modified by a silane coupling agent; 8-12 parts of a carbon fiber reinforcement phase; 1-3 parts of silicon dioxide; and 0.5 parts of other additives;

[0008] The surface of the ceramic nano-composite wire guide material is treated by ion bombardment to form a dense wear-resistant layer.

[0009] The present invention proposes a high-strength ceramic-based composite material and a preparation method and application thereof, which improves the wear resistance, interface bonding strength and friction coefficient of PP (polypropylene)-based composite materials, provides a material solution with better performance for applications in which textile yarn guides have high wear requirements, and greatly improves the service life and working reliability of textile yarn guides.

[0010] As a preferred technical solution, the other auxiliary agents include: any one or two of a heat stabilizer and an antioxidant.

[0011] As a preferred technical solution, functional groups are introduced on the surface of carbon fibers to form a carbon fiber reinforcement phase, and the functional groups include: carboxyl functional groups and hydroxyl functional groups.

[0012] On the other hand, the present invention provides a method for preparing a ceramic nanocomposite wire guide material, wherein the method comprises the following steps:

[0013] S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials;

[0014] S2: feeding the pretreated raw materials and other additives into a twin-screw extruder barrel according to the component proportions in parts by weight, performing melt mixing to fully disperse the components to obtain a molten mixture, extruding the molten mixture into a melt, and water-cooling and pelletizing the extruded melt to obtain composite material particles;

[0015] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product;

[0016] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product.

[0017] As a preferred technical solution, the polypropylene resin is pretreated in step S1, specifically comprising the following steps:

[0018] The polypropylene resin is vacuum dried at 110-120° C. for 4-6 hours, so that the residual moisture in the pretreated polypropylene resin is ≤0.03%.

[0019] As a preferred technical solution, the aluminum oxide nanoparticles are pretreated in step S1, specifically comprising the following steps:

[0020] Alumina nanoparticles are pretreated with gamma-aminopropyltriethoxysilane for surface modification, reacted at 85-90°C for 2.5-3 hours, with the amount of gamma-aminopropyltriethoxysilane accounting for 4-6% of the weight of the alumina nanoparticles, to obtain alumina nanoparticles surface modified with a silane coupling agent.

[0021] As a preferred technical solution, the carbon fiber is pretreated in step S1, specifically comprising the following steps:

[0022] The carbon fiber is pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 12-15V, and the time of the electrochemical anodization treatment is 25-30 minutes.

[0023] As a preferred technical solution, in step S3, the melting temperature of the composite material particles put into the barrel of the injection molding machine for injection molding is 230-240°C, the injection pressure is 110-120MPa, the holding time is 12-14 seconds, and the cooling time is 24-28 seconds.

[0024] As a preferred technical solution, in step S4, the ion energy of the ion bombardment surface treatment of the injection molded product is 90-100 keV and the time is 1.8-2.8 minutes.

[0025] On the other hand, the ceramic nanocomposite yarn guide material according to any one of the above items is used in a textile yarn guide.

[0026] The present invention provides a ceramic nanocomposite wire guide material and a preparation method and application thereof, which have the following beneficial effects:

[0027] 1) Improve the wear resistance, interface bonding strength and friction coefficient of PP (polypropylene) based composite materials, provide better material solutions for high wear requirements of textile yarn guides, and greatly improve the service life and working reliability of textile yarn guides;

[0028] 2) Alumina nanoparticles are surface-modified with a silane coupling agent to be used as fillers, thereby achieving strong chemical bonding between the alumina nanoparticles and the PP (polypropylene) matrix, effectively solving the problem of poor interface bonding between inorganic fillers and polymers, and significantly improving the interface bonding strength between the inorganic fillers and the polypropylene resin matrix, laying the foundation for improving the mechanical properties of ceramic nanocomposite wire guide materials. At the same time, the weight of alumina nanoparticles in the components is optimized, which greatly improves the wear resistance of the composite material and solves the problem of easy wear of traditional wire guide materials.

[0029] The addition of carbon fiber reinforcement further improves the mechanical properties of the composite material and meets the high strength requirements for use in textile yarn guides;

[0030] Ion bombardment treatment is used on the surface of the composite material to form a dense wear-resistant layer, which increases the roughness and chemical activity of the composite material surface and can further increase the friction coefficient to 0.42, meeting the requirements of the high-speed working environment of the textile guide;

[0031] Adding silica as a lubricant and surfactant can optimize the fluidity and surface quality of the composite material;

[0032] Add other additives to improve the comprehensive performance of composite materials;

[0033] Therefore, the present application achieves a synergistic effect by compounding the formula components of the ceramic nanocomposite wire guide material and optimizing the weight ratio of each component, thereby significantly improving the wear resistance, interface bonding strength and friction coefficient of the PP (polypropylene) based composite material, providing a material solution with better performance for the application field of textile wire guides with high wear requirements, and greatly improving the service life and working reliability of textile wire guides;

[0034] 3) Adopt optimized injection molding process parameters to ensure the surface quality and stable performance of composite products, avoid the defects of traditional processes, ensure the surface quality and dimensional accuracy of injection molded parts, and prepare wire guide materials with excellent wear resistance, high strength and stable friction performance;

[0035] 4) Through innovations in material formulation, material formulation ratio, material surface modification, process optimization, etc., a composite material for textile guides with excellent performance has been successfully developed. The ceramic nano-composite guide material products have been tested according to the standards of wear resistance (GB / T 1040.1), interface peeling strength (GB / T 7124), friction coefficient (GB / T 3960), etc. The test results show that the wear volume loss of the ceramic nano-composite guide material products is ≤49mm 3 / 1000r, the interfacial peeling strength between the aluminum oxide nanoparticles and the polypropylene matrix is ​​≥7.6MPa, and the dynamic friction coefficient is ≥0.42, which proves that the ceramic nanocomposite yarn guide material provided by the present invention and its preparation method and application can improve the wear resistance, interfacial bonding strength and friction coefficient of the PP (polypropylene)-based composite material, provide a material solution with better performance for the application field with high wear requirements of the textile yarn guide, and greatly improve the service life and working reliability of the textile yarn guide. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention are described in detail below.

[0037] The present invention provides a ceramic nanocomposite wire guide material, comprising the following components in parts by weight:

[0038] 60-70 parts of polypropylene resin; 20-25 parts of silane coupling agent surface modified aluminum oxide nanoparticles; 8-12 parts of carbon fiber reinforcement phase; 1-3 parts of silicon dioxide; 0.5 parts of other additives;

[0039] The surface of the ceramic nano-composite wire guide material is treated by ion bombardment to form a dense wear-resistant layer.

[0040] The present invention proposes a high-strength ceramic-based composite material and a preparation method and application thereof, which improves the wear resistance, interface bonding strength and friction coefficient of PP (polypropylene)-based composite materials, provides a material solution with better performance for applications in which textile yarn guides have high wear requirements, and greatly improves the service life and working reliability of textile yarn guides.

[0041] Preferably, the other auxiliary agents include: any one or both of a heat stabilizer and an antioxidant.

[0042] Preferably, functional groups are introduced on the surface of carbon fibers to form a carbon fiber reinforcement phase, and the functional groups include: carboxyl functional groups and hydroxyl functional groups.

[0043] The present invention provides a method for preparing a ceramic nanocomposite wire guide material, and the method comprises the following steps:

[0044] S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials;

[0045] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0046] The polypropylene resin is vacuum dried at 110-120°C for 4-6 hours, so that the residual moisture in the pretreated polypropylene resin is ≤0.03%;

[0047] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0048] Alumina nanoparticles are pretreated with γ-aminopropyltriethoxysilane for surface modification, reacted at 85-90° C. for 2.5-3 hours, with the amount of γ-aminopropyltriethoxysilane accounting for 4-6% of the weight of the alumina nanoparticles, to obtain alumina nanoparticles with silane coupling agent surface modified;

[0049] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0050] The carbon fiber is pretreated by electrochemical anodization: in a 10% sulfuric acid solution, carboxyl functional groups and hydroxyl functional groups are introduced into the surface of the carbon fiber, the voltage of the electrochemical anodization treatment is 12-15V, and the time of the electrochemical anodization treatment is 25-30 minutes;

[0051] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0052] The silicon dioxide raw material is fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0053] S2: feeding the pretreated raw materials and other additives into a twin-screw extruder barrel according to the component proportion in parts by weight, and performing melt mixing for 10-12 minutes at a melt temperature of 220-230° C. and a screw speed of 80-90 rpm to fully disperse the components to obtain a molten mixture, extruding the molten mixture into a melt, and water-cooling and pelletizing the extruded melt to obtain composite material particles;

[0054] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 230-240° C., the injection pressure is 110-120 MPa, the holding time is 12-14 seconds, and the cooling time is 24-28 seconds;

[0055] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 90-100 keV and the time is 1.8-2.8 minutes.

[0056] Application of the ceramic nanocomposite yarn guide material according to any one of the above items in a textile yarn guide.

[0057] Example 1

[0058] The present invention provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0059] S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials;

[0060] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0061] 60 parts by weight of polypropylene resin were vacuum dried at 110° C. for 6 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0062] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0063] 25 parts by weight of aluminum oxide nanoparticles are subjected to surface modification pretreatment using γ-aminopropyltriethoxysilane, and reacted at 90° C. for 2.5 hours, wherein the amount of γ-aminopropyltriethoxysilane used is 6% of the weight of the aluminum oxide nanoparticles, to obtain aluminum oxide nanoparticles surface-modified by a silane coupling agent;

[0064] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0065] 12 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0066] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0067] 2.5 parts by weight of silicon dioxide raw material are fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0068] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportions, and melt-mixed for 12 minutes at a melting temperature of 220° C. and a screw speed of 80 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0069] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 230° C., the injection pressure is 120 MPa, the holding time is 14 seconds, and the cooling time is 28 seconds;

[0070] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 90 keV and the time is 2.8 minutes.

[0071] The present invention provides a ceramic nano-composite wire guide material, which is prepared according to the above-mentioned method for preparing the ceramic nano-composite wire guide material.

[0072] The invention provides application of a ceramic nano-composite yarn guide material in a textile yarn guide.

[0073] Example 2

[0074] The present invention provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0075] S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials;

[0076] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0077] 70 parts by weight of polypropylene resin were vacuum dried at 120° C. for 4 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0078] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0079] 20 parts by weight of aluminum oxide nanoparticles are subjected to surface modification pretreatment by using γ-aminopropyltriethoxysilane, and reacted at 85° C. for 3 hours, wherein the amount of γ-aminopropyltriethoxysilane used is 4% of the weight of the aluminum oxide nanoparticles, to obtain aluminum oxide nanoparticles surface modified by a silane coupling agent;

[0080] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0081] 8 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0082] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0083] 1.5 parts by weight of a silicon dioxide raw material was fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0084] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportion of parts by weight, and melt-mixed for 10 minutes at a melt temperature of 230° C. and a screw speed of 90 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0085] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 240° C., the injection pressure is 110 MPa, the holding time is 12 seconds, and the cooling time is 24 seconds;

[0086] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 100 keV and the time is 1.8 minutes.

[0087] The present invention provides a ceramic nano-composite wire guide material, which is prepared according to the above-mentioned method for preparing the ceramic nano-composite wire guide material.

[0088] The invention provides application of a ceramic nano-composite yarn guide material in a textile yarn guide.

[0089] Comparative Example 1

[0090] Comparative Example 1 provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0091] S1 pre-treats polypropylene resin, carbon fiber and silicon dioxide respectively to obtain pre-treated raw materials;

[0092] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0093] 60 parts by weight of polypropylene resin were vacuum dried at 110° C. for 6 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0094] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0095] 12 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0096] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0097] 2.5 parts by weight of silicon dioxide raw material are fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0098] S2: putting the above-mentioned pretreated raw materials, 25 parts by weight of aluminum oxide nanoparticles and 0.5 parts by weight of other additives into the barrel of a twin-screw extruder, and performing melt mixing for 12 minutes at a melt temperature of 220° C. and a screw speed of 80 rpm to fully disperse the components to obtain a molten mixture, extruding the molten mixture into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0099] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 230° C., the injection pressure is 120 MPa, the holding time is 14 seconds, and the cooling time is 28 seconds;

[0100] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 90 keV and the time is 2.8 minutes.

[0101] Comparative Example 1 provides a ceramic nano-composite wire guide material, which is prepared according to the preparation method of the ceramic nano-composite wire guide material as described above.

[0102] Comparative Example 1 provides an application of a ceramic nanocomposite yarn guide material in a textile yarn guide.

[0103] Comparative Example 2

[0104] Comparative Example 2 provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0105] S1 pre-treats polypropylene resin, carbon fiber and silicon dioxide respectively to obtain pre-treated raw materials;

[0106] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0107] 60 parts by weight of polypropylene resin were vacuum dried at 110° C. for 6 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0108] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0109] 12 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0110] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0111] 2.5 parts by weight of silicon dioxide raw material are fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0112] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportions, and melt-mixed for 12 minutes at a melt temperature of 220° C. and a screw speed of 80 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0113] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 230° C., the injection pressure is 120 MPa, the holding time is 14 seconds, and the cooling time is 28 seconds;

[0114] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 90 keV and the time is 2.8 minutes.

[0115] Comparative Example 2 provides a ceramic nano-composite wire guide material, which is prepared according to the preparation method of the ceramic nano-composite wire guide material as described above.

[0116] Comparative Example 2 provides an application of a ceramic nanocomposite yarn guide material in a textile yarn guide.

[0117] Comparative Example 3

[0118] Comparative Example 3 provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0119] S1 pre-treats polypropylene resin, aluminum oxide microparticles, carbon fiber and silicon dioxide respectively to obtain pre-treated raw materials;

[0120] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0121] 60 parts by weight of polypropylene resin were vacuum dried at 110° C. for 6 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0122] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0123] 25 parts by weight of aluminum oxide micron particles are subjected to surface modification pretreatment using γ-aminopropyltriethoxysilane, and reacted at 90° C. for 2.5 hours, wherein the amount of γ-aminopropyltriethoxysilane used is 6% of the weight of the aluminum oxide micron particles, to obtain aluminum oxide micron particles surface modified with a silane coupling agent;

[0124] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0125] 12 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0126] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0127] 2.5 parts by weight of silicon dioxide raw material are fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0128] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportions, and melt-mixed for 12 minutes at a melting temperature of 220° C. and a screw speed of 80 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0129] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 230° C., the injection pressure is 120 MPa, the holding time is 14 seconds, and the cooling time is 28 seconds;

[0130] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 90 keV and the time is 2.8 minutes.

[0131] Comparative Example 3 provides a ceramic nano-composite wire guide material, which is prepared according to the preparation method of the ceramic nano-composite wire guide material as described above.

[0132] Comparative Example 3 provides an application of a ceramic nanocomposite yarn guide material in a textile yarn guide.

[0133] Comparative Example 4

[0134] Comparative Example 4 provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0135] S1 pre-treats polypropylene resin, aluminum oxide microparticles, carbon fiber and silicon dioxide respectively to obtain pre-treated raw materials;

[0136] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0137] 70 parts by weight of polypropylene resin were vacuum dried at 120° C. for 4 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0138] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0139] 20 parts by weight of aluminum oxide micron particles are subjected to surface modification pretreatment by using γ-aminopropyltriethoxysilane, and reacted at 85° C. for 3 hours, wherein the amount of γ-aminopropyltriethoxysilane used is 4% of the weight of the aluminum oxide micron particles, to obtain aluminum oxide micron particles surface modified by a silane coupling agent;

[0140] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0141] 8 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0142] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0143] 1.5 parts by weight of a silicon dioxide raw material was fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0144] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportion of parts by weight, and melt-mixed for 10 minutes at a melting temperature of 230° C. and a screw speed of 90 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0145] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 240° C., the injection pressure is 110 MPa, the holding time is 12 seconds, and the cooling time is 24 seconds;

[0146] S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product, wherein the ion energy of the ion bombardment surface treatment on the injection molded product is 100 keV and the time is 1.8 minutes.

[0147] Comparative Example 4 provides a ceramic nano-composite wire guide material, which is prepared according to the preparation method of the ceramic nano-composite wire guide material as described above.

[0148] Comparative Example 4 provides an application of a ceramic nanocomposite yarn guide material in a textile yarn guide.

[0149] Comparative Example 5

[0150] Comparative Example 5 provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0151] S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials;

[0152] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0153] 60 parts by weight of polypropylene resin were vacuum dried at 110° C. for 6 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0154] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0155] 25 parts by weight of aluminum oxide nanoparticles are subjected to surface modification pretreatment using γ-aminopropyltriethoxysilane, and the reaction is carried out at 90° C. for 2.5 hours, wherein the amount of γ-aminopropyltriethoxysilane used is 6% of the weight of the aluminum oxide nanoparticles, to obtain aluminum oxide nanoparticles surface-modified by a silane coupling agent;

[0156] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0157] 12 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0158] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0159] 2.5 parts by weight of silicon dioxide raw material are fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0160] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportions, and melt-mixed for 12 minutes at a melting temperature of 220° C. and a screw speed of 80 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0161] S3 puts the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles put into the barrel of an injection molding machine for injection molding is 230°C, the injection pressure is 120MPa, the holding time is 14 seconds, and the cooling time is 28 seconds.

[0162] Comparative Example 5 provides a ceramic nano-composite wire guide material, which is prepared according to the preparation method of the ceramic nano-composite wire guide material as described above.

[0163] Comparative Example 5 provides an application of a ceramic nano-composite yarn guide material in a textile yarn guide.

[0164] Comparative Example 6

[0165] Comparative Example 6 provides a method for preparing a ceramic nanocomposite wire guide material, comprising the following steps:

[0166] S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials;

[0167] In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps:

[0168] 60 parts by weight of polypropylene resin were vacuum dried at 110° C. for 6 hours, so that the residual moisture in the pretreated polypropylene resin was ≤0.03%;

[0169] In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps:

[0170] 25 parts by weight of aluminum oxide nanoparticles are subjected to surface modification pretreatment using γ-aminopropyltriethoxysilane, and the reaction is carried out at 90° C. for 2.5 hours, wherein the amount of γ-aminopropyltriethoxysilane used is 6% of the weight of the aluminum oxide nanoparticles, to obtain aluminum oxide nanoparticles surface-modified by a silane coupling agent;

[0171] In step S1, the carbon fiber is pretreated, which specifically comprises the following steps:

[0172] 12 parts by weight of carbon fiber are pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 15V, and the time of the electrochemical anodization treatment is 25 minutes;

[0173] In step S1, silicon dioxide is pretreated, which specifically comprises the following steps:

[0174] 2.5 parts by weight of silicon dioxide raw material are fully mixed with a high-speed stirrer to obtain silicon dioxide;

[0175] S2: the pretreated raw materials and 0.5 parts by weight of other additives are put into the barrel of a twin-screw extruder according to the component proportions, and melt-mixed for 12 minutes at a melting temperature of 220° C. and a screw speed of 80 rpm to fully disperse the components to obtain a molten mixture, and the molten mixture is extruded into a melt, and the extruded melt is water-cooled and pelletized to obtain composite material particles;

[0176] S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product, wherein the melting temperature of the composite material particles into the barrel of the injection molding machine for injection molding is 230° C., the injection pressure is 120 MPa, the holding time is 14 seconds, and the cooling time is 28 seconds;

[0177] S4 performs plasma surface treatment on the injection molded product.

[0178] Comparative Example 6 provides a ceramic nano-composite wire guide material, which is prepared according to the preparation method of the ceramic nano-composite wire guide material as described above.

[0179] Comparative Example 6 provides an application of a ceramic nano-composite yarn guide material in a textile yarn guide.

[0180] Experimental means of experimental data testing

[0181] The ceramic nanocomposite wire guide materials prepared in Examples 1-2 and Comparative Examples 1-6 were measured by the following experimental means:

[0182] The interfacial peeling strength between the aluminum oxide nanoparticles and the polypropylene matrix of Example 1 and Comparative Example 1 was tested by a tensile peeling test, and the test was conducted in accordance with GB / T 7124 standard.

[0183] According to GB / T 1040.1 standard, the wear resistance of the ceramic nanocomposite wire guide materials of Examples 1-2 and Comparative Examples 2-4 was tested using a ring-block wear tester, wherein the test conditions were: load of 500N, rotation speed of 500r / min, and wear time of 1000r;

[0184] According to GB / T 3960 standard, the dynamic friction coefficient of Example 1 and Comparative Examples 5-6 was tested using a ring-block friction tester. The test conditions were: load of 300N, sliding speed of 1m / s, and friction time of 30min.

[0185] The experimental data of the interfacial peeling strength test between the aluminum oxide nanoparticles and the polypropylene matrix in Example 1 and Comparative Example 1 are as follows in Table 1:

[0186] Table 1 Experimental data of interfacial peeling strength between aluminum oxide nanoparticles and polypropylene matrix in Example 1 and Comparative Example 1

[0187]

[0188] The experimental data of the wear resistance test of the ceramic nanocomposite wire guide materials of Examples 1-2 and Comparative Examples 2-4 are shown in Table 2 below:

[0189] Table 2 Experimental data of wear resistance test of ceramic nanocomposite wire guide materials of Examples 1-2 and Comparative Examples 2-4

[0190]

[0191]

[0192] The experimental data of the dynamic friction coefficient test of the ceramic nanocomposite wire guide materials of Example 1 and Comparative Examples 5-6 are shown in Table 3 below:

[0193] Table 3 Test data of dynamic friction coefficient of ceramic nanocomposite wire guide materials of Example 1 and Comparative Examples 5-6

[0194] name Composite material surface treatment Dynamic friction coefficient Example 1 Ion bombardment surface treatment 0.42 Comparative Example 5 Untreated surface 0.35 Comparative Example 6 Plasma surface treatment 0.40

[0195] From Table 1, we can observe that in the preparation steps of the ceramic nanocomposite guide wire material provided in Comparative Document 1, the aluminum oxide nanoparticles were not subjected to surface modification pretreatment, and the interfacial peeling strength between the aluminum oxide nanoparticles and the polypropylene matrix was 4.1 MPa; in the preparation steps of the ceramic nanocomposite guide wire material provided in Example 1 of the present application, the aluminum oxide nanoparticles were subjected to surface modification pretreatment using a silane coupling agent, and the interfacial peeling strength between the aluminum oxide nanoparticles and the polypropylene matrix was increased to 7.6 MPa, proving that the present application uses a silane coupling agent to perform surface modification treatment on the aluminum oxide nanoparticles, thereby improving the interfacial bonding strength of the PP (polypropylene)-based composite material.

[0196] From Table 2, we can see that in Comparative Example 2, alumina nanoparticles are not used as fillers, and the wear volume loss of the material product is 71 mm 3 / 1000r, in Example 1-2 of the present application, alumina nanoparticles are used as fillers, and the wear-resistant volume loss of the material product is reduced to 49mm 3 / 1000r, can significantly improve the wear resistance of the composite material, the use of aluminum oxide nanoparticles as fillers in Examples 1-2 of the present application is better than that of micron-sized aluminum oxide as fillers in the same weight content in Examples 3-4; this is because the aluminum oxide nanoparticles have a larger specific surface area and interface effect, which can more effectively hinder the cutting and peeling of abrasive particles; among them, the ceramic nanocomposite wire guide material with a weight content of 25 parts provided in the embodiments of the present application has the best wear resistance, and the wear-resistant volume loss of the material product is reduced to 42mm 3 / 1000r.

[0197] From Table 3, we can observe that in the preparation step of the ceramic nanocomposite guide wire material provided in Comparative Example 5, the material surface is not treated, and its dynamic friction coefficient is 0.35; in the preparation step of the ceramic nanocomposite guide wire material provided in Comparative Example 6, the material surface is treated by plasma, and its dynamic friction coefficient is 0.40; in the preparation step of the ceramic nanocomposite guide wire material provided in Example 1 of the present application, the material surface is treated by ion bombardment, and its dynamic friction coefficient is increased to 0.42, which is the best dynamic friction coefficient. This is because ion bombardment forms a dense wear-resistant layer on the surface of the composite material, increases the surface roughness and chemical activity, and thus improves the friction performance with the mating part.

[0198] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all various changes or equivalent substitutions falling within the scope of the claims of the present application are included. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present invention.

Claims

1. A ceramic nanocomposite wire guide material, characterized in that: The invention comprises the following components in parts by weight: 60-70 parts of polypropylene resin; 20-25 parts of aluminum oxide nanoparticles surface-modified by silane coupling agent; 8-12 parts of carbon fiber reinforcement phase; 1-3 parts of silicon dioxide; Other additives 0.5 parts; The surface of the ceramic nano-composite wire guide material is treated by ion bombardment to form a dense wear-resistant layer.

2. The ceramic nanocomposite wire guide material according to claim 1, characterized in that: The other auxiliary agents include: any one or both of a heat stabilizer and an antioxidant.

3. The ceramic nanocomposite wire guide material according to claim 1, characterized in that: Functional groups are introduced on the surface of carbon fibers to form a carbon fiber reinforcement phase, wherein the functional groups include carboxyl functional groups and hydroxyl functional groups.

4. A method for preparing a ceramic nanocomposite wire guide material, characterized in that: The ceramic nanocomposite wire guide material according to any one of claims 1 to 3 is prepared, comprising the following steps: S1 pre-treats polypropylene resin, aluminum oxide nanoparticles, carbon fibers and silicon dioxide respectively to obtain pre-treated raw materials; S2: feeding the pretreated raw materials and other additives into a twin-screw extruder barrel according to the component proportions in parts by weight, performing melt mixing to fully disperse the components to obtain a molten mixture, extruding the molten mixture into a melt, and water-cooling and pelletizing the extruded melt to obtain composite material particles; S3: putting the composite material particles into the barrel of an injection molding machine for injection molding to obtain an injection molded product; S4 performs ion bombardment surface treatment on the injection molded product to form a dense wear-resistant layer on the surface of the injection molded product.

5. The method for preparing the ceramic nanocomposite wire guide material according to claim 4, characterized in that: In step S1, polypropylene resin is pre-treated, which specifically comprises the following steps: The polypropylene resin is vacuum dried at 110-120° C. for 4-6 hours, so that the residual moisture in the pretreated polypropylene resin is ≤0.03%.

6. The method for preparing a ceramic nanocomposite wire guide material according to claim 4, characterized in that: In step S1, the aluminum oxide nanoparticles are pretreated, which specifically includes the following steps: Alumina nanoparticles are pretreated with gamma-aminopropyltriethoxysilane for surface modification, reacted at 85-90°C for 2.5-3 hours, with the amount of gamma-aminopropyltriethoxysilane accounting for 4-6% of the weight of the alumina nanoparticles, to obtain alumina nanoparticles surface modified with a silane coupling agent.

7. The method for preparing a ceramic nanocomposite wire guide material according to claim 4, characterized in that: In step S1, the carbon fiber is pretreated, which specifically comprises the following steps: The carbon fiber is pretreated by electrochemical anodization: carboxyl functional groups and hydroxyl functional groups are introduced to the surface of the carbon fiber in a 10% sulfuric acid solution, the voltage of the electrochemical anodization treatment is 12-15V, and the time of the electrochemical anodization treatment is 25-30 minutes.

8. The method for preparing a ceramic nanocomposite wire guide material according to claim 4, characterized in that: In step S3, the composite material particles are put into the barrel of the injection molding machine for injection molding at a melting temperature of 230-240° C., an injection pressure of 110-120 MPa, a holding time of 12-14 seconds, and a cooling time of 24-28 seconds.

9. The method for preparing a ceramic nanocomposite wire guide material according to claim 4, characterized in that: In step S4, the injection molded product is subjected to ion bombardment surface treatment with an ion energy of 90-100 keV and a time of 1.8-2.8 minutes.

10. Use of the ceramic nanocomposite yarn guide material according to any one of claims 1 to 3 in a textile yarn guide.

Citation Information

Patent Citations

  • High-strength wear-resistant polypropylene compound and preparation method thereof

    CN109721829A

  • High-wear-resistance ceramic enhanced polymer composite material and preparation method thereof

    CN119320527A

  • Carbon fiber-reinforced thermoplastic resin molding and carbon fiber-reinforced thermoplastic resin molding material

    JP2016190922A

  • High-pressure-resistant pipeline plastic and preparation method therefor

    WO2023123070A1